Forming project budget for financial and economic literacy for children of preschool and primary school age using Microsoft Office Project - Totska, Olesia Leontiivna; Тоцька, Олеся Леонтіївна (Державна наукова установа «Інститут освітньої аналітики», 2022)
The financial services market is developing rapidly in today’s dynamic world. The financial inclusion of our compatriots directly depends on their financial and economic literacy. Therefore, awareness of Ukrainian citizens with financial and economic terms, as well as the basics of financial transactions should take place in childhood. The aim of the article is to draw up the budget of the educational project of financial and economic literacy for the children of preschool and primary school age with the help of the Microsoft Office Project. The article describes the features of the project (purpose, existing hierarchical goals, coordinated implementation of related actions, time frame, availability of the budget, uniqueness). The project of financial and economic literacy for the children is classified into certain types of projects according to different classification criteria (scale, duration, industry affiliation, functional direction, the nature of the parties involved, the degree of complexity, the composition and structure of the organizations involved, the requirements for project quality, the degree of binding, the degree of communication, the number of participants). The step-by-step algorithm of project development from the establishment of the project team to project budget formulation is created and described. Methods used: SWOT-analysis (to identify strengths and weaknesses, threats and opportunities of the project), critical path (for planning project works), budgeting (for project budgeting). The algorithm of automated scheduling of project tasks in the Microsoft Office Project program is described. The project budget includes the costs of printing presentation materials; creating drawings to explain the financial and economic terms that will be used in the children’s book; creating a layout and printing a children’s book; creating a cartoon; creating a project web page; remuneration of teachers for conducting training sessions. The time frame of the project was 5,5 months. The universality of the project is indicated, as it can be implemented by teachers of economic departments of any institution of higher education in Ukraine. It is noted that the developed project of financial and economic literacy for the children can serve as a basis for other educational projects in preschool or school education or for similar projects of financial and economic literacy, where the target audience will be middle and high school students studying in general secondary education institutions, gymnasiums, lyceums.
Формування бюджету проєкту фінансово-економічної грамотності для дітей дошкільного та молодшого шкільного віку засобами Microsoft Office Project
Ринок фінансових послуг стрімко розвивається в сучасному динамічному світі. Фінансова інклюзія наших співвітчизників безпосередньо залежить від їх фінансово-економічної грамотності. Тому знайомство громадян України з фінансовими й економічними термінами, а також основами здійснення фінансових операцій повинно відбуватися ще в дитячі роки. Метою статті є формування бюджету освітнього проєкту фінансово-економічної грамотності для дітей дошкільного та молодшого шкільного віку за допомогою програми Microsoft Office Project. У статті описано ознаки проєкту (мету, наявні ієрархічні цілі, координоване виконання пов’язаних між собою дій, часові рамки, наявність бюджету, унікальність). Проєкт фінансово-економічної грамотності для дітей віднесено до певних видів проєктів за різними класифікаційними ознаками (масштабом, тривалістю, галузевою приналежністю, функціональним спрямуванням, характером залучених сторін, ступенем складності, складом і структурою залучених організацій, вимогами до якості проєкту, ступенем обов’язковості, ступенем зв’язку, кількістю учасників). Поетапний алгоритм розроблення проєкту від формування команди проєкту до формування бюджету проєкту сформовано й описано. Використано методи: SWOT-аналіз (для визначення сильних і слабких сторін, загроз і можливостей проєкту), критичного шляху (для планування робіт проєкту), бюджетування (для формування бюджету проєкту). Описано алгоритм автоматизованого планування задач проєкту в програмі Microsoft Office Project. До бюджету проєкту включено витрати на друк презентаційних матеріалів; створення малюнків для пояснення фінансових й економічних термінів, що будуть використані в дитячій книзі; створення макету та друк дитячої книги; створення мультфільму; створення веб-сторінки проєкту; оплату праці викладачів за проведення навчальних занять. Часові рамки проєкту склали 5,5 місяців. Вказано на універсальності проєкту, оскільки його можуть реалізувати викладачі кафедр економічного профілю будь-якого закладу вищої освіти України. Відзначено, що розроблений проєкт фінансово-економічної грамотності для дітей може слугувати основою для інших освітніх проєктів у сфері дошкільної чи шкільної освіти або для аналогічних проєктів фінансово-економічної грамотності, де цільовою аудиторією будуть учні середніх і старших класів, які навчаються в закладах загальної середньої освіти, гімназіях, ліцеях.
Keywords: budget; project; financial and economic literacy; children of preschool and primary school age; Microsoft Office Project; бюджет; проєкт; фінансово-економічна грамотність; діти дошкільного та молодшого шкільного віку; Microsoft Office Project; G00; Н60; С88; J15; J24; 336:005.336.2:[004.4-027.22:005.8]:373.2/.3